A spatial analysis of monetary and non-monetary poverty in Cameroon between 2001 and 2014 - TIOMELA YEMEDJEU Alexis; NGASSA NYA Yves Daniel; NKEMGHA ZEUFACK GUIVIS (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
The objective of this study is to analyze the spatial distribution of monetary and non-monetary poverty in Cameroon. The identification of poor households by the monetary dimension is done using the thresholds defined by national institute of statistics. While in the non-monetary, dimension we use multiple correspondence analysis to construct composite indicators of well-being. After calculating the composite indicators, we use the formula developed by Ki et al. (2005) to calculate the poverty line. The data used in this study is from the second, third and fourth Cameroon household surveys. The results show that the incidence of monetary poverty declined from 40.2% in 2001 to 39.9% in 2007 to reach 37.5% in 2014. Non-monetary poverty stagnated between 2001 and 2007, with the incidence going from 60.65% to 61%. In 2014, the incidence declined to 53.84%. The proportion of individuals affected by both monetary and non-monetary poverty increased from 34.34% in 2001 to 35.59% in 2007, and stood at 33.49% in 2014. The rural areas are the most affected by monetary and non-monetary poverty. The region of the country most affected by monetary and non-monetary poverty is the Far North. Taking into account these results, poverty reduction policies in Cameroon should give priority to rural areas. Thus specific measures should be taken to improve access to basic infrastructures in rural areas. The Cameroonian government can also reduce taxes on construction materials.